Low Prevalence of Isolated Growth Hormone Deficiency in Patients After Brain Injury: Results From a Phase II Pilot Study - Leonhardt, Miriam; Kopczak, Anna; Schäpers, Barbara; Limbrock, Janina; Sämann, Philipp G.; Czisch, Michael; von Steinbuechel, Nicole; Jordan, Martina; Schneider, Harald J.; Schneider, Manfred; Sievers, Caroline; Stalla, Günter K. (Frontiers in Endocrinology, 2018)
Growth hormone deficiency (GHD) results in an impaired health-related quality of life (HrQoL) and cognitive impairment in the attention and memory domain. GHD is assumed to be a frequent finding after brain injury due to traumatic brain injury (TBI), aneurysmal subarachnoid hemorrhage (SAH) or ischemic stroke. Hence, we set out to investigate the effects of growth hormone (GH) replacement therapy in patients with isolated GHD after brain injury on HrQoL, cognition, and abdominal fat composition. In total, 1,408 patients with TBI, SAH or ischemic stroke were screened for inclusion. Of those, 54 patients (age 18–65 years) were eligible, and 51 could be tested for GHD with GHRH-L-arginine. In 6 patients (12%), GHD was detected. All patients with isolated GHD (n=4 [8%], male, mean age ± SD: 49.0 ± 9.8 years) received GH replacement therapy for 6 months at a daily dose of 0.2–0.5 mg recombinant GH depending on age. Results were compared with an untreated control group of patients without hormonal insufficiencies after brain injury (n=6, male, mean age ± SD: 49.5 ± 13.6 years). HrQoL as well as mood and sleep quality assessed by self-rating questionnaires (Beck Depression Index, Pittsburgh Sleep Quality Index) did not differ between baseline and 6 months within each group or between the two groups. Similarly, cognitive performance as assessed by standardized memory and attention tests did not show significant differences within or between groups. Body mass index was higher in the control vs. the GH replacement group at baseline (p=0.038), yet not different at 6 months and within groups. Visceral-fat-by-total-fat-ratio measurements obtained from magnetic resonance imaging in 2 patients and 5 control subjects exhibited no consistent pattern. In conclusion, this single center study revealed a prevalence of GHD of about 12% (8% with isolated GHD) in brain injury patients which was lower compared with most of the previously reported cohorts. As a consequence, the sample size was insufficient to conclude on a benefit or no benefit of GH replacement in patients with isolated GHD after brain injury. A higher number of patients will be necessary to draw conclusions in future studies.